Oxygen assisted H2O dissociation on the Pt{110}(1 × 2) surface from first principles - Ranea, Victor Alejandro (2014)
Water dissociation with and without oxygen coadsorption is investigated on the Pt{110}(1 × 2) surface at low coverage from first principles. Calculations indicate that desorption of the water molecule is likely to occur fromthe clean surface ahead of partial dissociation. The assistance of coadsorbed atomic O in the H2O partial dissociation changes the picture. Several H2O+O→OH+ OH possible reactions (with no OH+ H + O intermediate step) have been analyzed. The comparison between the activation energy for the mentioned reaction and the activation energy for H2O desorption shows no strong preference for one reaction over the other one. These results predict that the partial dissociation of H2O is a likely process if it is assisted by atomic O on the Pt {110}(1 × 2) surface. Dissociation and desorption of the H2O molecule are competitive processes on the surface and is possible to predict a dynamic system.